Child Protection from Cyber Violence: An Analysis of CRC General Comment No. 25 and Contemporary Islamic Ethical Perspectives in Indonesia and Malaysia - Rizki Adi Pinandito; Hartiwiningsih; Muhammad Rustamaji (Faculty of Sharia, UIN Jurai Siwo Lampung, 2026)
The research aims to analyze the extent to which both countries have developed regulatory and institutional mechanisms to safeguard children from digital harm and to formulate an integrative model of protection that aligns international child rights standards with contemporary Islamic ethical values. In this context, Islamic ethical principles derived from maqāṣid al-sharī‘ah are positioned as a normative foundation for strengthening digital child protection. This research employs normative or doctrinal legal research using statutory, conceptual, and comparative approaches to examine relevant legal norms, principles, and doctrines in Indonesia and Malaysia, alongside the ethical framework of maqāṣid al-sharī‘ah. The findings indicate that the regulatory framework for child protection from cyber violence in Indonesia has shown normative progress and policy alignment with the CRC and General Comment No. 25, yet its implementation remains partial and fragmented. In comparison, Malaysia demonstrates relatively more structured institutional coordination in addressing online risks to children. Based on this comparative synthesis, the study proposes an ideal ius constituendum model of integrative and coherent protection through a systemic risk-based regulatory design grounded in the principles of maṣlaḥah and sadd al-dharā’i (harm prevention), while reinforcing justice (‘adl) through equal service standards, including for children in remote and disadvantaged regions. Academically, this study contributes to the development of contemporary Islamic legal scholarship by bridging international child rights standards with Islamic ethical principles in the context of digital governance. It also offers a conceptual framework for integrating CRC/GC25 norms with maqāṣid al-sharī‘ah as a complementary ethical foundation for shaping responsive, culturally grounded cyber child protection policies in Muslim-majority societies.